Evidence for Categories of Laughter - Hegarty, Katie; Esposito, Anna; Koutsombogera, Maria; Vogel, Carl (ISCA, 2024)
A binary classification of laughter according to a functional dimension of venting mirth vs. moving discourse along is considered in relation to a three-way social classification of any instance of laughter as solo, ratifying or ratified (the latter two understood as shared laughter). Tests of these classifications with an extant dialogue data set are conducted in order to assess whether they interact: significant interaction is taken as evidence that the categorizations are informative. Interactions with other phenomena, like personality traits, are similarly assessed. Each cross-classification reveals significant interactions.
Laughter and Other Non-Verbal Vocalisations Workshop 2024
Keywords: laughter, dialogue, computational linguistics; classification, discourse laughter, ratified laughter, paralinguistics; Digital Humanities; Artificial Intelligence; Computational Linguistics; Discourse & Dialogue; Discourse markers; laughter